KONTRIBUSI NORMALISASI HYSTERETIC ENERGY TERHADAP DAMAGE INDEX DI PADA RESPONS INELASTIK STRUKTUR SDOF AKIBAT GEMPA - Widodo; Malik Mushthofa (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2023)
At a relatively large earthquake ground acceleration, the response of the structure is no longer elastic but is already in the inelastic phase where hysteretic energy is one of the elements of the earthquake energy content. In this phase, structural damage can not be avoided and structural damage is generally expressed in term of damage index DI. Studies on the contribution of normalization of hysteretic energy to the SDOF structure have been carried out. The inelastic behavior of the structure is simulated according to the behavior of Modified Takeda hysteretic model. In this study, two variables were used, namely the earthquake frequency content which is expressed in term of A/V ratio and the vibration period of the structure T. The results showed that the lower the value of the A/V ratio tends to result in a greater damage index DI, both for relatively rigid structures and for relatively flexible structures. The more flexible a structure tends to experience a greater damage index DI both for earthquakes high, medium and low frequency. The contribution of normalization of hysteretic energy to the damage index DI ranges from 10-30%, and the more flexible the structure, the contribution of normalization of hysteretic energy will be smaller. Furthermore, there is also a tendency that the lower the earthquake frequency content, the smaller the contribution of normalized hysteretic energy will accordingly.